Suara Sunyi Leluhur: Melekatnya Kontrol Sosial Berbasis Budaya Pamali pada Masyarakat Kabupaten Belu - Arni Enggelina Ello (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2026)
This study explores the role of pamali culture as a non-formal mechanism of social control in Belu Regency, East Nusa Tenggara. As a border community exposed to modernization and foreign cultural influences, the Belu people continue to preserve ancestral oral traditions as behavioral guidance in daily life. Using a qualitative phenomenological approach, data were collected through in-depth interviews, observation, and documentation. Informants were selected purposively, including customary elders and community members who had lived in Belu for at least 20 years. Data were analyzed through the epoche method to maintain the authenticity of informants' subjective experiences. The findings show that pamali prohibitions, such as shaking one's legs while eating, standing around doorways, and whistling at night, have been internalized across generations as part of collective consciousness. Viewed through Anthony Giddens' Structuration Theory and Pierre Bourdieu's Habitus Theory, pamali functions not only as a set of prohibitions but also as embodied disposition and self-censorship. Unlike social control based on a single leader's authority, pamali in Belu operates in a decentralized, voluntary, and democratic manner. The study concludes that pamali remains adaptive in maintaining harmony, reducing deviance, and protecting public morality from modernity's negative effects.